2017
DOI: 10.5230/jgc.2017.17.e35
|View full text |Cite
|
Sign up to set email alerts
|

Greater Lymph Node Retrieval Improves Survival in Node-Negative Resected Gastric Cancer in the United States

Abstract: PurposeGuidelines in western countries recommend retrieving ≥15 lymph nodes (LNs) during gastric cancer resection. This study sought to determine whether the number of examined lymph nodes (eLNs), a proxy for lymphadenectomy, effects survival in node-negative disease.Materials and MethodsThe US National Cancer Database (2003–2011) was reviewed for node-negative gastric adenocarcinoma. Treatment was categorized by neoadjuvant therapy (NAT) vs. initial resection, and further stratified by eLN. Kaplan-Meier and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…16,17 Mirkin et al published a study relying on the National Cancer Data Base, which captures over 70% of the newly diagnosed cancer patients in the United States. 10 In their study, as many as 60% of the patients undergoing gastrectomy for gastric cancer had 15 lymph nodes or less examined by the pathologist. CI, confidence interval; HGD, high-grade dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Mirkin et al published a study relying on the National Cancer Data Base, which captures over 70% of the newly diagnosed cancer patients in the United States. 10 In their study, as many as 60% of the patients undergoing gastrectomy for gastric cancer had 15 lymph nodes or less examined by the pathologist. CI, confidence interval; HGD, high-grade dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Still, in a significant proportion of gastric resections the goal of pathologically examining at least 15 lymph nodes is not achieved. 10 While there is an agreement as to the minimum number of lymph nodes required for appropriate assessment, only a few studies have evaluated the factors associated with achieving this goal. This study's main objective was to examine how many surgeries indeed succeed in resecting an adequate number of lymph nodes and to evaluate possible factors associated with inadequate lymph node resection.…”
Section: Introductionmentioning
confidence: 99%
“…12 The most likely contributor is the much greater number of lymph nodes retrieved at FMUUH (median 32 vs 16 at BCH). Greater lymph node retrieval has been associated with better survival in numerous studies, 15,16 including one in China. 17 Another key difference is that the prior study included patients with fewer than 15 LNs retrieved, which may have resulted in underestimation of N category preferentially among Chinese cases, where retrieval of few lymph nodes was more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The most likely contributor is the much greater number of lymph nodes retrieved at FMUUH (median 32 vs. 16 at BCH). Greater lymph node retrieval has been associated with better survival in numerous studies,[15,16] including one in China. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Prior work by Mirkin et al demonstrated that an inadequate lymphadenectomy of fewer than 11 lymph nodes among patients undergoing neoadjuvant therapy resulted in significantly worse survival for patients with stage III gastric cancer; however, in patients who underwent surgical resection first-line therapy, inadequate lymphadenectomy was also associated with worse survival outcomes in stage I and II disease, suggesting that inadequate lymphadenectomy has prognostic implications regardless of initial therapy. 2 An institutional analysis by Ho et al 3 in patients with surgically resected esophageal cancer who underwent NACT demonstrated that an increase in the number of lymph nodes retrieved (more than 21) was associated with improved survival, suggesting that utilization of NACT may influence the number of regional lymph nodes necessary for optimal prognostication. Conceptually, NACT may yield complete pathologic responses in lymph nodes, which may increase the number of evaluated lymph nodes necessary for improved prognostication, but how this influences lymph node retrieval in patients with gastric cancer specifically, remains understudied.…”
mentioning
confidence: 99%